Osmium isotopic composition and platinum group element concentrations in sediments from ODP Hole 145-886C - Gregory E Ravizza (PANGAEA, 2007)
Paired analyses of Os isotope composition and concentration of bulk sediment and leachable Os in a metalliferous pelagic clay sequence from the North Pacific, ODP Site 886C, are used to reconstruct the marine Os isotope record and the particulate meteoritic Os flux between 65.5 and 78 Ma. Measured 187Os/188Os of bulk sediments ranges from approximately 0.64 to 0.32 and those of leach analyses are very similar to bulk analyses. Hydrogenous Os dominates the sedimentary Os inventory throughout most of the studied interval. As a result the measured 187Os/188Os of leachable Os approximates that of contemporaneous seawater. The ODP 886C record shows rising 187Os/188Os in the deepest portion of the core, with a local maximum of 0.66 close to 74 Ma. The 67-72 Ma portion of the record is characterized by nearly constant 187Os/188Os ratios close to 0.6. The structure of the marine Os isotope record from ODP 886C differs markedly from the seawater 87Sr/86Sr curve, which rises monotonically throughout the time interval studied here. Calculated particulate meteoritic Os fluxes are between 0.5 and 2 pg/cm**2/kyr throughout most of the studied interval. Two discrete intervals of the core (one of which is within Cretaceous Tertiary, boundary KTB interval) are characterized by higher fluxes of meteoritic Os. Excluding these two intervals, the average background flux of particulate meteoritic Os is roughly half of that estimated from analyses of Cenozoic marine sediments. These are the first Os isotope data to provide evidence of resolvable temporal variations in the background flux of particulate meteoritic material to the Earth.
Supplement to: Ravizza, GE (2007): Reconstructing the marine 187Os/188Os record and the particulate flux of meteoritic osmium during the Late Cretaceous. Geochimica et Cosmochimica Acta, 71(5), 1355-1369, https://doi.org/10.1016/j.gca.2006.11.006